KONSEP TASWIYAH AL-NAFS DALAM PENGEMBANGAN PRIBADI MANUSIA - Hamdie, Ilham Masykuri (UIN Antasari Banjarmasin, 2017)
The manifestation of human superiority as ?ahsan al-taqwim? can be interpreted as the process of developing the level of